Sertifikasi Aeo dan Perputaran Persediaan: Analisis Komparatif Perusahaan di Indonesia - Fitriyaning Putri Nastiti; Henryanto Wijaya (CV. Green Publisher Indonesia, 2026)
This study examines the impact of Authorized Economic Operator (AEO) certification on inventory turnover and whether firm size influences differences in inventory performance among listed companies in Indonesia. The background of this research is based on the increasing adoption of AEO certification as a trade facilitation mechanism intended to enhance supply chain efficiency, despite mixed evidence regarding its operational benefits. The objective of this study is to analyze differences in inventory turnover before and after AEO certification and to test whether such differences vary between large and small firms. This research employs a quantitative approach using a before-and-after comparative design. The sample consists of 10 companies listed on the Indonesia Stock Exchange that have held AEO status for at least three years. Data were obtained from financial statements and analyzed using paired sample t-test and independent sample t-test with SPSS software. The results show a statistically significant difference in inventory turnover before and after AEO certification, but the direction indicates a decline in turnover after certification. This suggests that the expected efficiency gains from AEO implementation are not immediately realized. Furthermore, the analysis reveals no significant difference in inventory turnover changes between large and small firms. The findings imply that compliance costs, organizational adjustment, and external disruptions such as supply chain shocks may offset the benefits of certification in the short term. The study concludes that the effectiveness of AEO certification on operational efficiency may require a longer time horizon to become evident.